Two-component quick-drying antiskid self-cleaning road marking coating and preparation method thereof
By adopting a two-component formula in road marking coatings, combined with functional components such as aqueous polyurethane dispersion, light-responsive self-healing microcapsules, iron-doped nanotitanium dioxide, etc., the shortcomings of traditional coatings in durability, anti-slip properties and self-cleaning properties are solved, and high-performance, multifunctional and environmentally friendly road marking coatings are achieved.
Patent Information
- Application Number
- CN202411870537.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-18
AI Technical Summary
Traditional road marking coatings produce harmful gases during construction, lack durability and early water resistance, poor anti-slip performance and self-cleaning ability, inability to self-repair, and degraded performance in extreme weather conditions, resulting in high road maintenance costs and safety threats.
Two-component fast-drying anti-slip self-cleaning road marking coating is used to organically combine functional components such as aqueous polyurethane dispersion, light-responsive self-repair microcapsules, iron-doped nanotitanium dioxide, surface-modified anti-slip particles, multifunctional silane coupling agents through carefully designed formula and preparation process to achieve long-term anti-slip, self-cleaning and self-repair functions of the coating.
It achieves the perfect combination of quick drying and durability of the coating, provides excellent anti-slip performance and long-lasting self-cleaning effect, extends the service life of the coating, adapts to various extreme environments, and meets environmental protection requirements.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a two-component quick-drying anti-skid self-cleaning road marking coating and a preparation method thereof. Background Art
[0002] As an important part of traffic safety, road marking plays a vital role in improving road traffic efficiency and reducing traffic accident rates. However, with the continuous increase in traffic flow and the complex changes in environmental factors, traditional road marking paints face many challenges.
[0003] First, although conventional hot-melt road marking paint has good wear resistance, a large amount of harmful gases are generated during its construction, which does not meet modern environmental protection requirements. Secondly, although water-based road marking paint is environmentally friendly, its durability and early water resistance are often unsatisfactory. Furthermore, existing road marking paints generally have problems such as insufficient anti-slip performance, poor self-cleaning ability, and inability to self-repair, which seriously affect the service life and function of road markings.
[0004] In addition, under extreme weather conditions, such as high or low temperatures or rainy environments, the performance of traditional road marking paints tends to drop sharply. For example, in cold areas, the paint is prone to cracking due to temperature changes; in rainy areas, the anti-skid performance and water resistance of the paint face severe tests; and in hot areas, the paint is prone to softening and deformation. These problems not only increase road maintenance costs, but more importantly, threaten the safety of road users.
[0005] Although there are some improvement schemes in the prior art, such as adding inorganic fillers to improve wear resistance, or using special resins to improve adhesion, etc., these methods often lose sight of one thing while focusing on another, and it is difficult to simultaneously meet the requirements of quick drying, anti-slip, self-cleaning, self-repairing, durability, etc. In particular, in terms of self-repairing and long-term self-cleaning, the prior art still has obvious deficiencies.
[0006] Therefore, it is urgent to develop new road marking coatings that can comprehensively solve the above problems to meet the urgent needs of modern transportation construction for high-performance, multifunctional and environmentally friendly road marking materials. Summary of the invention
[0007] The present invention aims to solve the following technical problems: how to improve the durability and early water resistance of the coating while ensuring its quick drying; how to achieve the long-term anti-skid and self-cleaning functions of the coating; how to give the coating self-repairing ability and extend its service life; how to improve the adaptability of the coating in various extreme environments; how to ensure the environmental protection and construction convenience of the coating while meeting the above requirements. In response to these technical problems, the present invention proposes a two-component quick-drying anti-skid self-cleaning road marking paint and a preparation method thereof. The coating cleverly combines multiple functional components through a carefully designed formula and preparation process, achieving synergistic enhancement between the components.
[0008] The object of the present invention is to provide a two-component quick-drying anti-skid self-cleaning road marking paint, comprising component A and component B, wherein: Component A is made from the following raw materials in parts by weight: 30-50 parts of waterborne polyurethane dispersion Photoresponsive self-repairing microcapsules 5-10 copies 3-8 parts of iron-doped nano titanium dioxide 8-15 parts of surface modified anti-skid particles Multifunctional silane coupling agent 1-3 parts pH adjuster 0.1-0.5 parts Bio-based defoamer 0.2-0.6 parts Intelligent temperature sensitive thickener 0.5-1.5 parts Broad-spectrum antibacterial agent 0.1-0.3 parts 10-40 parts of deionized water Component B is made from the following raw materials in parts by weight: 20-40 parts of water-dispersible isocyanate curing agent Hyperbranched polyether modifier 5-15 parts 1-3 parts of hydrophobic nano-silica Light stabilizer 0.5-1.5 parts 40-70 parts of deionized water.
[0009] Specifically, the aqueous polyurethane dispersion has a solid content of 40 ± 1%, a pH value of 7.0-8.5, a viscosity (23°C) of 50-800 mPa·s, and an average particle size of 80-120 nm; The multifunctional silane coupling agent is N-[3-(trimethoxysilyl)propyl]-1,2-ethylenediamine, with a boiling point of 260°C, a flash point of 93°C, and a density (25°C) of 1.03 g / cm³.
[0010] Specifically, the pH adjuster is ammonium hydroxide in a 28% aqueous solution; The broad-spectrum antibacterial agent is a mixture of 1,2-benzisothiazol-3(2H)-one and 2-methyl-4-isothiazoline-3-one, wherein the content of 1,2-benzisothiazol-3(2H)-one is 10-15%, and the content of 2-methyl-4-isothiazoline-3-one is 2-5%.
[0011] Specifically, the hyperbranched polyether modifier has a hydroxyl value of 230-250 mg KOH / g and a viscosity (23°C) of 3000-5000 mPa·s; The hydrophobic nano-silica is pyrolytic silica treated with hexamethyldisilazane, with a specific surface area of 195-245 m² / g, an average particle size of 7 nm, and a carbon content of 3.0-4.0%.
[0012] Specifically, The active ingredient content of the light stabilizer is 52-56%, and the pH value is 6.0-8.0; The water-dispersible isocyanate curing agent is a water dispersion of hexamethylene diisocyanate, with an NCO content of 16.5-17.5% and a viscosity (23°C) of 500-2500 mPa·s.
[0013] The preparation method of the two-component quick-drying anti-skid self-cleaning road marking paint comprises the following steps: (1) Preparation of component A: First, add waterborne polyurethane dispersion into the reactor and stir at a speed of 300-400 rpm; Secondly, add the photoresponsive self-healing microcapsules and stir for 30 minutes; Then, iron-doped nano-titanium dioxide was added and stirred for 45 minutes; Again, add the surface modified anti-skid particles and stir for 30 minutes; Next, add the multifunctional silane coupling agent, pH adjuster, bio-based defoamer and intelligent temperature-sensitive thickener in sequence, stirring for 10 minutes after each addition of raw materials; Finally, a broad-spectrum antimicrobial agent was added, stirred for 15 minutes, and deionized water was added to adjust the solid content to 55-60%, stirred for 30 minutes, and filtered through a 100-mesh sieve to obtain component A; (2) Preparation of component B: First, add water-dispersible isocyanate curing agent into the reaction kettle and stir at a speed of 200-300 rpm; Secondly, add the hyperbranched polyether modifier and stir for 20 minutes; Then, hydrophobic nano-silica was added and stirred for 30 minutes; Again, add the light stabilizer and stir for 15 minutes; Finally, deionized water was added to adjust the solid content to 40-45%, stirred for 20 minutes, and filtered through a 200-mesh sieve to obtain component B.
[0014] Specifically, the method for preparing the light-responsive self-repairing microcapsules comprises the following steps: (1) preparing an oil phase: mixing 5-10 parts by weight of dicyclopentadiene and 0.1-0.3 parts by weight of a light-responsive Grubbs catalyst at 20-25° C., stirring at a speed of 300-400 rpm for 15-20 minutes; (2) preparing an aqueous phase: dissolving 1-2 parts by weight of polyvinyl alcohol in 100-150 parts by weight of deionized water, stirring at a speed of 500-600 rpm, a temperature of 60-70° C., and a time of 30-40 minutes; (3) preparing a monomer mixture: mixing 15-25 parts by weight of methyl methacrylate and 1-3 parts by weight of glycidyl methacrylate, and adding 0.2-0.5 parts by weight of azobisisobutyronitrile; (4) Emulsification: slowly add the oil phase into the water phase and shear emulsify at 60-70°C at a speed of 1000-1200 rpm for 15-20 minutes; (5) Suspension polymerization: Slowly add the monomer mixture dropwise into the emulsion and react at 70-75°C with stirring (400-500 rpm) for 3-4 hours; (6) Cooling: Cooling the reaction mixture to room temperature; (7) Filtration, washing, and drying: Filter using a Buchner funnel, wash with deionized water 3-5 times, and vacuum dry at 40-50°C for 12-24 hours.
[0015] Specifically, the preparation method of iron-doped nano titanium dioxide comprises the following steps: (1) Preparation of precursor solution: dissolve 20-30 parts by weight of tetrabutyl titanate in 80-100 parts by weight of anhydrous ethanol, stir at 300-400 rpm, and stir at room temperature for 30 minutes; at the same time, dissolve 0.5-1.5 parts by weight of ferric nitrate in 20-30 parts by weight of deionized water; (2) Hydrolysis: slowly add the iron salt solution to the titanate solution, increase the stirring speed to 600-800 rpm, and react at room temperature for 1-2 hours; (3) Aging: The mixture was aged at 60-70°C with stirring (200-300 rpm) for 4-6 hours; (4) Hydrothermal treatment: the aged sol is transferred to a polytetrafluoroethylene-lined autoclave and treated at 180-200°C for 8-12 hours; (5) Cooling, filtering, and washing: Cool naturally to room temperature, filter, and wash with deionized water and anhydrous ethanol 3-5 times each; (6) Drying and calcining: drying at 60-70°C for 12-24 hours, and then calcining at 400-500°C for 2-3 hours; (7) Grinding: Grind the calcined sample to an average particle size of 20-30 nm.
[0016] Specifically, the preparation method of the surface-modified anti-skid particles comprises the following steps: (1) Pretreatment: 100 parts by weight of α-alumina was vacuum dried at 120-130° C. for 4-6 hours; (2) Silanization: Add the pretreated alumina and 200-250 parts by weight of anhydrous toluene to a three-necked flask, stir and disperse (300-400 rpm) for 10-15 minutes; slowly add 3-5 parts by weight of 3-glycidyloxypropyltrimethoxysilane, raise the temperature to reflux (about 110-120°C), and stir and react for 4-6 hours; (3) Cooling and filtration: Cool naturally to room temperature and filter; (4) Washing: Wash with anhydrous toluene 3 times, then wash with anhydrous ethanol 2 times; (5) Drying: Vacuum drying at 60-70°C for 12-24 hours.
[0017] Specifically, the preparation method of the intelligent temperature-sensitive thickener comprises the following steps: (1) Preparation of monomer solution: In a three-necked flask, 15-20 parts by weight of N-isopropylacrylamide and 1-2 parts by weight of acrylamide are dissolved in 150-200 parts by weight of deionized water, and nitrogen is passed through for 15-20 minutes to remove oxygen; (2) Preparation of initiator solution: dissolve 0.1-0.2 parts by weight of ammonium persulfate in 10-15 parts by weight of deionized water; (3) Polymerization reaction: Heat the monomer solution to 60-65°C and control the stirring speed at 300-400 rpm; slowly add the initiator solution dropwise and react for 4-6 hours; (4) Termination of the reaction: Cool the reaction mixture to room temperature and allow air to flow for 10-15 minutes; (5) Purification: The reaction product was poured into excess acetone for precipitation, filtered, and washed with acetone three times; (6) Drying: Vacuum drying at 40-50°C for 24-48 hours.
[0018] Specifically, the core innovations of the present invention and its mechanism of action are as follows: 1. Combination of waterborne polyurethane dispersion and water-dispersible isocyanate curing agent: These two components form a cross-linked network structure at the molecular level. The hydroxyl group (-OH) on the polyurethane molecular chain reacts with the -NCO group of isocyanate to form a hydrolysis-resistant urea bond (-NHCOO-), which not only provides excellent film-forming properties and adhesion, but also greatly improves the water resistance and durability of the coating.
[0019] 2. Photoresponsive self-healing microcapsules: These microcapsules contain dicyclopentadiene monomers and photoresponsive Grubbs catalysts. When the coating is damaged, the microcapsules rupture to release the contents. Under ultraviolet light, the catalyst is activated, initiating the ring-opening metathesis polymerization of dicyclopentadiene, thereby repairing the cracks. This process does not require external intervention, greatly extending the service life of the coating.
[0020] 3. Iron-doped nano-titanium dioxide: By doping with iron ions, the light response range of titanium dioxide is broadened, so that it can also play a photocatalytic role under visible light. When light irradiates the coating surface, iron-doped titanium dioxide generates electron-hole pairs, which in turn generate active oxygen species (such as ·OH, ·O 2- ). These active species can effectively decompose organic pollutants and realize the self-cleaning function of the coating.
[0021] 4. Surface modified anti-skid particles: The surface modification of alumina particles by silane coupling agent not only improves the compatibility of particles with polyurethane matrix, but also forms a microscopic rough structure on the coating surface. This structure significantly increases the friction coefficient and provides excellent anti-skid performance. At the same time, silane modification also enhances the bonding force between particles and matrix and improves the overall mechanical properties of the coating.
[0022] 5. Intelligent temperature-sensitive thickener: Poly(N-isopropylacrylamide-co-acrylamide) copolymer has a low critical solution temperature (LCST) characteristic. At low temperatures, the polymer chain stretches to provide good fluidity; when the temperature rises, the polymer chain shrinks to form a cross-linked network and increase the viscosity of the coating. This intelligent response not only improves the construction performance, but also provides additional anti-slip effect in the use environment.
[0023] 6. Hyperbranched polyether modifier: Its unique tree-like molecular structure provides a large number of terminal functional groups, increasing the interaction points with other components. This not only improves the crosslinking density of the coating, but also enhances its flexibility and low-temperature adaptability. At the same time, the microscopic phase separation structure formed by the hyperbranched structure helps to improve the weather resistance and self-cleaning durability of the coating.
[0024] 7. Hydrophobic nano-silica: Through hexamethyldisilazane treatment, this nanoparticle forms a micro-nanoscale rough structure on the coating surface. Combined with the low surface energy characteristics of the material itself, the super-hydrophobic effect of the coating surface is achieved. This not only enhances the self-cleaning ability, but also improves the stain resistance and durability of the coating.
[0025] These innovative components form a highly synergistic multifunctional system in the coating through precise formula design and preparation process. For example, the repairing effect of the self-healing microcapsules and the self-cleaning function of iron-doped titanium dioxide promote each other and extend the service life of the coating. The combination of intelligent temperature-sensitive thickener and surface-modified anti-slip particles can ensure excellent anti-slip performance under different temperature conditions.
[0026] The beneficial effects of the present invention include: 1. The perfect combination of quick-drying and durability achieves the dual goals of fast traffic and long-term use; 2. Excellent anti-skid performance, significantly improving road safety; 3. Long-lasting self-cleaning effect greatly reduces maintenance costs; 4. Unique self-repairing function greatly extends the service life of the coating; 5. Excellent environmental adaptability, can maintain stable performance under various extreme climatic conditions; 6. Environmentally friendly water-based system reduces VOC emissions and meets the requirements of sustainable development; 7. Intelligent temperature-sensitive characteristics improve construction performance and provide additional functional advantages.
[0027] In short, the present invention not only solves many problems faced by traditional road marking paints through the organic combination of multiple innovative technologies, but also achieves many unexpected technical effects. This high-performance, multifunctional, and environmentally friendly road marking paint will surely provide strong technical support for modern transportation construction and road safety. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] In the coating of the present invention, the waterborne polyurethane dispersion is selected from BayhydrolUH 2558 waterborne polyurethane dispersion of Covestro (formerly Bayer MaterialScience), with a solid content of 40 ± 1%, a pH value of 7.0-8.5, a viscosity (23°C) of 50-800 mPa·s, and an average particle size of 80-120 nm; The multifunctional silane coupling agent is GENIOSIL® GF 91 from Wacker Chemical Company, which is N-[3-(trimethoxysilyl)propyl]-1,2-ethylenediamine, with a boiling point of 260°C, a flash point of 93°C, and a density (25°C) of 1.03 g / cm³.
[0030] The pH regulator is ammonium hydroxide, which is a 28% aqueous solution, that is, ammonia water; The broad-spectrum antimicrobial agent is BIOBAN™ 551S from Dow Chemical Company, which is a mixture of 1,2-benzisothiazol-3(2H)-one (BIT) and 2-methyl-4-isothiazoline-3-one MIT, wherein the content of 1,2-benzisothiazol-3(2H)-one is 10-15%, and the content of 2-methyl-4-isothiazoline-3-one is 2-5%.
[0031] The hyperbranched polyether modifier is Boltorn™ H311 from BASF, with a hydroxyl value of 230-250 mgKOH / g and a viscosity (23°C) of 3000-5000 mPa·s; The hydrophobic nano-silica is AEROSIL ® R812S is pyrogenic silica treated with hexamethyldisilazane, with a surface area of 195-245 m² / g, an average particle size of 7 nm, and a carbon content of 3.0-4.0%.
[0032] The light stabilizer is Tinuvin produced by BASF ® 5333-DW, active ingredient content is 52-56%, pH value is 6.0-8.0; The water-dispersible isocyanate curing agent is Bayhydur 3100 from Covestro, which is a water dispersion of hexamethylene diisocyanate with an NCO content of 16.5-17.5% and a viscosity (23°C) of 500-2500 mPa·s.
[0033] The method for preparing the light-responsive self-repairing microcapsules comprises the following steps: (1) preparing an oil phase: mixing 5-10 parts by weight of dicyclopentadiene and 0.1-0.3 parts by weight of a light-responsive Grubbs catalyst at 20-25° C., stirring at a speed of 300-400 rpm for 15-20 minutes; (2) preparing an aqueous phase: dissolving 1-2 parts by weight of polyvinyl alcohol in 100-150 parts by weight of deionized water, stirring at a speed of 500-600 rpm, a temperature of 60-70° C., and a time of 30-40 minutes; (3) preparing a monomer mixture: mixing 15-25 parts by weight of methyl methacrylate and 1-3 parts by weight of glycidyl methacrylate, and adding 0.2-0.5 parts by weight of azobisisobutyronitrile; (4) Emulsification: slowly add the oil phase into the water phase and shear emulsify at 60-70°C at a speed of 1000-1200 rpm for 15-20 minutes; (5) Suspension polymerization: Slowly add the monomer mixture dropwise into the emulsion and react at 70-75°C with stirring (400-500 rpm) for 3-4 hours; (6) Cooling: Cooling the reaction mixture to room temperature; (7) Filtration, washing, and drying: Filter using a Buchner funnel, wash with deionized water 3-5 times, and vacuum dry at 40-50°C for 12-24 hours.
[0034] The preparation method of the iron-doped nano titanium dioxide comprises the following steps: (1) Preparation of precursor solution: dissolve 20-30 parts by weight of tetrabutyl titanate in 80-100 parts by weight of anhydrous ethanol, stir at 300-400 rpm, and stir at room temperature for 30 minutes; at the same time, dissolve 0.5-1.5 parts by weight of ferric nitrate in 20-30 parts by weight of deionized water; (2) Hydrolysis: slowly add the iron salt solution to the titanate solution, increase the stirring speed to 600-800 rpm, and react at room temperature for 1-2 hours; (3) Aging: The mixture was aged at 60-70°C with stirring (200-300 rpm) for 4-6 hours; (4) Hydrothermal treatment: the aged sol is transferred to a polytetrafluoroethylene-lined autoclave and treated at 180-200°C for 8-12 hours; (5) Cooling, filtering, and washing: Cool naturally to room temperature, filter, and wash with deionized water and anhydrous ethanol 3-5 times each; (6) Drying and calcining: drying at 60-70°C for 12-24 hours, and then calcining at 400-500°C for 2-3 hours; (7) Grinding: Grind the calcined sample to an average particle size of 20-30 nm.
[0035] The preparation method of the surface-modified anti-skid particles comprises the following steps: (1) Pretreatment: 100 parts by weight of α-alumina was vacuum dried at 120-130° C. for 4-6 hours; (2) Silanization: Add the pretreated alumina and 200-250 parts by weight of anhydrous toluene to a three-necked flask, stir and disperse (300-400 rpm) for 10-15 minutes; slowly add 3-5 parts by weight of 3-glycidyloxypropyltrimethoxysilane, raise the temperature to reflux (about 110-120°C), and stir and react for 4-6 hours; (3) Cooling and filtration: Cool naturally to room temperature and filter; (4) Washing: Wash with anhydrous toluene 3 times, then wash with anhydrous ethanol 2 times; (5) Drying: Vacuum drying at 60-70°C for 12-24 hours. Example
[0036] The two-component quick-drying anti-skid self-cleaning road marking paint of this embodiment includes component A and component B.
[0037] Component A is made from the following raw materials in parts by weight: 30 parts of waterborne polyurethane dispersion Photoresponsive self-healing microcapsules 5 copies 3 parts of iron-doped nano-titanium dioxide 8 parts of surface modified anti-skid particles 1 multifunctional silane coupling agent pH adjuster 0.1 part 0.2 parts of bio-based defoamer 0.5 parts of intelligent temperature-sensitive thickener Broad-spectrum antibacterial agent 0.1 part 40 parts of deionized water Component B is made from the following raw materials in parts by weight: 20 parts of water-dispersible isocyanate curing agent 5 parts of hyperbranched polyether modifier 1 part hydrophobic nano silica Light stabilizer 0.5 parts 70 parts of deionized water.
[0038] The preparation method of this embodiment comprises the following steps: (1) Preparation of component A: First, 30 parts of aqueous polyurethane dispersion (solid content 40%, pH value 7.0, viscosity 75mPa·s, average particle size 100nm) were added to the reactor with a stirring speed of 300rpm; secondly, 5 parts of light-responsive self-healing microcapsules were added and stirred for 30 minutes; then, 3 parts of iron-doped nano-titanium dioxide (iron doping amount 0.5wt%, specific surface area 80m² / g) were added and stirred for 45 minutes; again, 8 parts of surface-modified anti-slip particles (surface silanization degree 1.5 μmol / m²) were added and stirred for 30 minutes; then, 1 part of multifunctional silane coupling agent, 0.1 part of pH regulator, 0.2 part of bio-based defoamer and 0.5 part of intelligent temperature-sensitive thickener (weight average molecular weight 100,000) were added in sequence. g / mol, LCST is 32°C), stirring for 10 minutes after each addition of raw materials; finally, 0.1 parts of a broad-spectrum antibacterial agent was added, stirred for 15 minutes, and 40 parts of deionized water were added to adjust the solid content to 55%, stirred for 30 minutes, and filtered through a 100-mesh sieve to obtain component A.
[0039] (2) Preparation of component B: First, 20 parts of water-dispersible isocyanate curing agent (NCO content 16.5%, viscosity 500mPa·s) were added to the reactor, and the stirring speed was 200rpm; secondly, 5 parts of hyperbranched polyether modifier (hydroxyl value 230 mg KOH / g, viscosity 3000mPa·s) were added and stirred for 20 minutes; then, 1 part of hydrophobic nano-silica (specific surface area 195 m² / g, carbon content 3.0%) was added and stirred for 30 minutes; again, 0.5 parts of light stabilizer (active ingredient content 52%, pH value 6.0) was added and stirred for 15 minutes; finally, 70 parts of deionized water were added to adjust the solid content to 40%, stirred for 20 minutes, and filtered through a 200-mesh sieve to obtain component B.
[0040] Preferably, in an embodiment of the present invention, an aqueous polyurethane dispersion is used as the main film-forming substance, providing excellent film-forming properties and adhesion. Light-responsive self-healing microcapsules can trigger a self-healing process under ultraviolet light irradiation, and work in conjunction with iron-doped nano-titanium dioxide to achieve a perfect combination of self-cleaning and self-healing functions, significantly extending the service life of the coating. The surface-modified anti-slip particles work together with the multifunctional silane coupling agent to not only improve the anti-slip properties of the coating, but also enhance the overall mechanical properties. The intelligent temperature-sensitive thickener maintains good fluidity during construction and increases viscosity during use, further enhancing the anti-slip effect and durability of the coating. Example
[0041] The two-component quick-drying anti-skid self-cleaning road marking paint of this embodiment includes component A and component B.
[0042] Component A is made from the following raw materials in parts by weight: 40 parts of waterborne polyurethane dispersion Photoresponsive self-healing microcapsules 7.5 parts 5.5 parts of iron-doped nano-titanium dioxide Surface modified anti-skid particles 11.5 parts 2 copies of multifunctional silane coupling agent pH adjuster 0.3 parts 0.4 parts of bio-based defoamer 1 part of intelligent temperature-sensitive thickener 0.2 parts of broad-spectrum antibacterial agent 25 parts deionized water Component B is made from the following raw materials in parts by weight: 30 parts of water-dispersible isocyanate curing agent Hyperbranched polyether modifier 10 parts 2 parts of hydrophobic nano-silica Light stabilizer 1 part 55 parts of deionized water.
[0043] The preparation method of this embodiment comprises the following steps: (1) Preparation of component A: First, 40 parts of aqueous polyurethane dispersion (solid content 40.5%, pH value 7.5, viscosity 425mPa·s, average particle size 100nm) were added to the reactor at a stirring speed of 350rpm; secondly, 7.5 parts of light-responsive self-healing microcapsules were added and stirred for 30 minutes; then, 5.5 parts of iron-doped nano-titanium dioxide (iron doping amount 1wt%, specific surface area 100m² / g) were added and stirred for 45 minutes; again, 11.5 parts of surface-modified anti-slip particles (surface silanization degree 2 μmol / m²) were added and stirred for 30 minutes; then, 2 parts of multifunctional silane coupling agent, 0.3 parts of pH regulator, 0.4 parts of bio-based defoamer and 1 part of intelligent temperature-sensitive thickener (weight average molecular weight 125,000) were added in sequence. g / mol, LCST is 33°C), stirring for 10 minutes after each addition of raw materials; finally, 0.2 parts of a broad-spectrum antibacterial agent was added, stirred for 15 minutes, and 25 parts of deionized water were added to adjust the solid content to 57.5%, stirred for 30 minutes, and filtered through a 100-mesh sieve to obtain component A.
[0044] (2) Preparation of component B: First, 30 parts of water-dispersible isocyanate curing agent (NCO content 17%, viscosity 1500mPa·s) were added to the reactor at a stirring speed of 250rpm; secondly, 10 parts of hyperbranched polyether modifier (hydroxyl value 240 mg KOH / g, viscosity 4000 mPa·s) were added and stirred for 20 minutes; then, 2 parts of hydrophobic nano-silica (specific surface area 220 m² / g, carbon content 3.5%) were added and stirred for 30 minutes; again, 1 part of light stabilizer (active ingredient content 54%, pH value 7.0) was added and stirred for 15 minutes; finally, 55 parts of deionized water were added to adjust the solid content to 42.5%, stirred for 20 minutes, and filtered through a 200-mesh sieve to obtain component B.
[0045] In this embodiment, by increasing the amount of aqueous polyurethane dispersion and adjusting its physical parameters, the film-forming performance and durability of the coating are further improved. The content of iron-doped nano-titanium dioxide is increased, which enhances the photocatalytic self-cleaning effect of the coating. At the same time, the amount of surface-modified anti-skid particles is increased, which significantly improves the anti-skid performance of the coating.
[0046] Example 3: Two-component quick-drying anti-skid self-cleaning road marking paint The two-component quick-drying anti-skid self-cleaning road marking paint of this embodiment includes component A and component B.
[0047] Component A is made from the following raw materials in parts by weight: 50 parts of waterborne polyurethane dispersion Photoresponsive self-healing microcapsules 10 copies 8 parts of iron-doped nano-titanium dioxide Surface modified anti-skid particles 15 parts 3 parts of multifunctional silane coupling agent pH adjuster 0.5 parts 0.6 parts of bio-based defoamer 1.5 parts of intelligent temperature-sensitive thickener 0.3 parts of broad-spectrum antibacterial agent 10 parts of deionized water; Component B is made from the following raw materials in parts by weight: 40 parts of water-dispersible isocyanate curing agent Hyperbranched polyether modifier 15 parts 3 parts of hydrophobic nano-silica Light stabilizer 1.5 parts 40 parts of deionized water.
[0048] The preparation method of this embodiment comprises the following steps: (1) Preparation of component A: First, 50 parts of aqueous polyurethane dispersion (solid content 41%, pH value 8.5, viscosity 775mPa·s, average particle size 120 nm) were added to the reactor with a stirring speed of 400rpm; secondly, 10 parts of light-responsive self-healing microcapsules were added and stirred for 30 minutes; then, 8 parts of iron-doped nano-titanium dioxide (iron doping amount 1.5wt%, specific surface area 120 m² / g) were added and stirred for 45 minutes; again, 15 parts of surface-modified anti-slip particles (surface silanization degree 2.5 μmol / m²) were added and stirred for 30 minutes; then, 3 parts of multifunctional silane coupling agent, 0.5 parts of pH regulator, 0.6 parts of bio-based defoamer and 1.5 parts of intelligent temperature-sensitive thickener (weight average molecular weight 150,000) were added in sequence. g / mol, LCST is 34°C), stirring for 10 minutes after each addition of raw materials; finally, 0.3 parts of a broad-spectrum antibacterial agent was added, stirred for 15 minutes, and 10 parts of deionized water were added to adjust the solid content to 60%, stirred for 30 minutes, and filtered through a 100-mesh sieve to obtain component A.
[0049] (2) Preparation of component B: First, 40 parts of water-dispersible isocyanate curing agent (NCO content 17.5%, viscosity 2500mPa·s) were added to the reactor, and the stirring speed was 300rpm; secondly, 15 parts of hyperbranched polyether modifier (hydroxyl value 250 mg KOH / g, viscosity 5000 mPa·s) were added and stirred for 20 minutes; then, 3 parts of hydrophobic nano-silica (specific surface area 245 m² / g, carbon content 4.0%) were added and stirred for 30 minutes; again, 1.5 parts of light stabilizer (active ingredient content 56%, pH value 8.0) were added and stirred for 15 minutes; finally, 40 parts of deionized water were added to adjust the solid content to 45%, stirred for 20 minutes, and filtered through a 200-mesh sieve to obtain component B.
[0050] In this embodiment, the self-repairing ability and durability of the coating are significantly enhanced by increasing the dosage of the aqueous polyurethane dispersion and the light-responsive self-repairing microcapsules to the maximum. At the same time, the dosage of iron-doped nano-titanium dioxide and surface-modified anti-skid particles is also maximized, further improving the self-cleaning effect and anti-skid performance of the coating. The increased dosage of the multifunctional silane coupling agent helps to improve the adhesion of the coating to various road materials. Example
[0051] The two-component quick-drying anti-skid self-cleaning road marking paint of this embodiment includes component A and component B.
[0052] Component A is made from the following raw materials in parts by weight: 45 parts of waterborne polyurethane dispersion Photoresponsive self-repairing microcapsules 8 copies 6 parts of iron-doped nano-titanium dioxide Surface modified anti-skid particles 12 parts 2.5 parts of multifunctional silane coupling agent pH adjuster 0.4 parts 0.5 parts of bio-based defoamer 1.2 parts of intelligent temperature-sensitive thickener 0.25 parts of broad-spectrum antibacterial agent 20 parts of deionized water; Component B is made from the following raw materials in parts by weight: 35 parts of water-dispersible isocyanate curing agent Hyperbranched polyether modifier 12 parts 2.5 parts of hydrophobic nano-silica Light stabilizer 1.2 parts 50 parts of deionized water.
[0053] The preparation method of this embodiment comprises the following steps: (1) Preparation of component A: First, 45 parts of aqueous polyurethane dispersion (solid content 40.8%, pH value 8.0, viscosity 600mPa·s, average particle size 110 nm) were added to the reactor at a stirring speed of 375rpm; secondly, 8 parts of light-responsive self-healing microcapsules were added and stirred for 30 minutes; then, 6 parts of iron-doped nano-titanium dioxide (iron doping amount 1.2wt%, specific surface area 110 m² / g) were added and stirred for 45 minutes; again, 12 parts of surface-modified anti-slip particles (surface silanization degree 2.2 μmol / m²) were added and stirred for 30 minutes; then, 2.5 parts of multifunctional silane coupling agent, 0.4 parts of pH regulator, 0.5 parts of bio-based defoamer and 1.2 parts of intelligent temperature-sensitive thickener (weight average molecular weight 135,000 g / mol, LCST is 33.5°C), stirring for 10 minutes after each addition of raw materials; finally, 0.25 parts of a broad-spectrum antibacterial agent was added, stirred for 15 minutes, and 20 parts of deionized water were added to adjust the solid content to 58.5%, stirred for 30 minutes, and filtered through a 100-mesh sieve to obtain component A.
[0054] (2) Preparation of component B: First, 35 parts of water-dispersible isocyanate curing agent (NCO content 17.2%, viscosity 2000mPa·s) were added to the reactor, and the stirring speed was 275rpm; secondly, 12 parts of hyperbranched polyether modifier (hydroxyl value 245 mg KOH / g, viscosity 4500 mPa·s) were added and stirred for 20 minutes; then, 2.5 parts of hydrophobic nano-silica (specific surface area 230 m² / g, carbon content 3.7%) were added and stirred for 30 minutes; again, 1.2 parts of light stabilizer (active ingredient content 55%, pH value 7.5) were added and stirred for 15 minutes; finally, 50 parts of deionized water were added to adjust the solid content to 43.5%, stirred for 20 minutes, and filtered through a 200-mesh sieve to obtain component B.
[0055] In this embodiment, the overall balance of performance is achieved by optimizing and adjusting the dosage of each component and the physical parameters. The dosage of the waterborne polyurethane dispersion and the light-responsive self-healing microcapsules is moderate, ensuring that the coating has good film-forming properties and self-healing ability. The content of iron-doped nano-titanium dioxide is slightly higher than the middle value, providing an excellent photocatalytic self-cleaning effect. The dosage of the surface-modified anti-skid particles is also at a medium level, ensuring the anti-skid performance without affecting other properties of the coating.
[0056] It is worth noting that the intelligent temperature-sensitive thickener in this embodiment has a weight average molecular weight of 135,000 g / mol and a LCST of 33.5°C, which allows the coating to have appropriate fluidity during construction and can rapidly thicken at the use temperature, providing excellent anti-slip performance. At the same time, the increased amount of hyperbranched polyether modifier further improves the crosslinking density and flexibility of the coating, making it more adaptable to temperature changes and mechanical stresses in the road environment.
[0057] Through the above four embodiments, the two-component quick-drying anti-skid self-cleaning road marking paint of the present invention fully demonstrates its excellent performance and wide applicability.
[0058] For example, Example 1 represents a basic formula, which is suitable for general road conditions; Example 2 improves the durability and anti-skid performance of the coating by increasing the content of functional components, and is suitable for roads with heavy traffic; Example 3 represents a high-performance formula, which is suitable for extreme climates or heavy traffic conditions; and Example 4 is a balanced formula that balances various performance properties and can be widely used in various road environments.
[0059] This flexibility enables the coating of the present invention to be customized according to the climate conditions, traffic volume and road type of different regions, providing a comprehensive solution for road marking. At the same time, by adjusting the parameters in the preparation process, such as stirring speed, reaction temperature and time, the performance of the coating can be further optimized to meet more stringent application requirements.
[0060] In general, these four embodiments fully demonstrate the technical characteristics and advantages of the two-component quick-drying anti-skid self-cleaning road marking paint of the present invention, and fully reflect its innovation and practicality in the field of road marking.
[0061] Comparative Example 1: Two-component road marking paint lacking light-responsive self-repairing microcapsules The coating formulation of this comparative example is based on Example 1, but the photoresponsive self-healing microcapsules are removed to verify the effect of this component on the self-healing properties of the coating.
[0062] Component A is made from the following raw materials in parts by weight: 30 parts of waterborne polyurethane dispersion, 3 parts of iron-doped nano titanium dioxide, 8 parts of surface-modified anti-slip particles, 1 part of multifunctional silane coupling agent, 0.1 part of pH adjuster, 0.2 part of bio-based defoamer, 0.5 part of intelligent temperature-sensitive thickener, 0.1 part of broad-spectrum antibacterial agent, and 45 parts of deionized water.
[0063] The formulation of component B is the same as that of Example 1.
[0064] The preparation method is basically the same as that of Example 1, except that the step of adding light-responsive self-repairing microcapsules is omitted when preparing component A.
[0065] Through comparative tests, it was found that although the coating still has certain anti-slip and self-cleaning properties, the tiny scratches and cracks on the surface cannot be repaired by themselves during long-term use, resulting in a gradual decline in coating performance. This result fully demonstrates the key role of light-responsive self-healing microcapsules in extending the service life of coatings.
[0066] Comparative Example 2: Two-component road marking paint using ordinary titanium dioxide instead of iron-doped nano-titanium dioxide This comparative example is based on Example 2, except that the iron-doped nano-titanium dioxide is replaced with ordinary titanium dioxide to verify the effect of iron doping on the photocatalytic self-cleaning effect.
[0067] In the formula of component A, 5.5 parts of iron-doped nano-titanium dioxide were replaced with 5.5 parts of common nano-titanium dioxide (average particle size 25 nm, specific surface area 50 m² / g). The formula of other components and component B was the same as that of Example 2.
[0068] The preparation method is basically the same as that of Example 2, except that ordinary nano titanium dioxide is used instead of iron-doped nano titanium dioxide when adding titanium dioxide.
[0069] The test results show that although the coating still has a certain self-cleaning ability, its photocatalytic efficiency under visible light is significantly reduced. This shows that iron doping not only expands the light response range of titanium dioxide, but also improves its catalytic activity under visible light, thereby enhancing the self-cleaning effect of the coating. In addition, iron-doped nano-titanium dioxide also produces a synergistic effect with self-healing microcapsules, further improving the durability of the coating.
[0070] Comparative Example 3: Two-component road marking paint without surface modified anti-skid particles This comparative example is based on Example 3, except that the surface-modified anti-skid particles are removed to verify the contribution of this component to the anti-skid performance of the coating.
[0071] In the formulation of component A, 15 parts of surface-modified anti-skid particles were removed, and the amount of aqueous polyurethane dispersion was increased to 65 parts. The formulation of other components and component B was the same as that of Example 3.
[0072] The preparation method is substantially the same as that of Example 3, except that the step of adding the surface-modified anti-skid particles is omitted.
[0073] The test results show that while the other properties of the coating remain basically unchanged, the anti-skid performance is significantly reduced. In particular, under wet conditions, the friction coefficient is reduced by about 40%. This fully demonstrates the important role of surface-modified anti-skid particles in improving the anti-skid performance of the coating. At the same time, due to the lack of synergistic effects of anti-skid particles and multifunctional silane coupling agents, the overall mechanical properties of the coating are also reduced.
[0074] Comparative Example 4: Two-component road marking paint using conventional thickener instead of intelligent temperature-sensitive thickener This comparative example is based on Example 4, except that the intelligent temperature-sensitive thickener is replaced with a conventional polyacrylic acid thickener to verify the unique effect of the intelligent temperature-sensitive thickener.
[0075] In the formula of component A, 1.2 parts of the intelligent temperature-sensitive thickener are replaced with 1.2 parts of a polyacrylic acid thickener (molecular weight of about 200,000). The formula of other components and component B is the same as that of Example 4.
[0076] The preparation method is substantially the same as that of Example 4, except that a polyacrylic acid thickener is used instead of the intelligent temperature-sensitive thickener when adding the thickener.
[0077] The test results show that the coating using conventional thickeners has poor fluidity during construction and is not easy to apply evenly. At the same time, under high temperature conditions, the viscosity of the coating decreases significantly, resulting in reduced anti-slip performance. This fully demonstrates the unique advantages of intelligent temperature-sensitive thickeners in adjusting the rheological properties of coatings, which not only ensures the convenience of construction, but also provides stable anti-slip performance under the use environment.
[0078] Comparative Example 5: Two-component road marking paint without hyperbranched polyether modifier This comparative example is based on Example 1, except that the hyperbranched polyether modifier in component B is removed to verify the effect of this component on the crosslinking density and flexibility of the coating.
[0079] In the formulation of component B, 5 parts of the hyperbranched polyether modifier were removed, and the water-dispersible isocyanate curing agent was increased to 25 parts accordingly. The formulation of component A was the same as that of Example 1.
[0080] The preparation method is substantially the same as that of Example 1, except that the step of adding the hyperbranched polyether modifier is omitted when preparing component B.
[0081] The test results show that although the initial performance of the coating is good, after multiple temperature cycle tests, the coating showed obvious cracking and shedding. This shows that the hyperbranched polyether modifier plays a key role in improving the crosslinking density and flexibility of the coating, enabling the coating to better adapt to the temperature changes and mechanical stress of the road environment.
[0082] Comparative Example 6: Two-component road marking paint without hydrophobic nano-silica This comparative example is based on Example 2, but removes the hydrophobic nano-silica in component B to verify the effect of this component on the self-cleaning durability of the coating.
[0083] In the formula of component B, 2 parts of hydrophobic nano-silicon dioxide were removed, and deionized water was increased to 57 parts accordingly. The formula of component A was the same as that of Example 2.
[0084] The preparation method is substantially the same as that of Example 2, except that the step of adding hydrophobic nano-silica is omitted when preparing component B.
[0085] The long-term exposure test results show that although the coating initially exhibits good self-cleaning effects, the self-cleaning ability decreases significantly over time. This is because the coating surface cannot maintain long-term hydrophobicity due to the lack of hydrophobic nano-silica, making it easier for pollutants to adhere. This result fully demonstrates the important role of hydrophobic nano-silica in maintaining the long-term self-cleaning performance of the coating.
[0086] Through these six comparative examples, we can clearly see the unique role and synergistic effect of each key component in the present invention. The introduction of innovative components such as light-responsive self-repairing microcapsules, iron-doped nano-titanium dioxide, surface-modified anti-skid particles, intelligent temperature-sensitive thickeners, hyperbranched polyether modifiers and hydrophobic nano-silica makes the two-component quick-drying anti-skid self-cleaning road marking paint of the present invention show obvious advantages in self-repairing ability, photocatalytic self-cleaning effect, anti-skid performance, construction convenience, environmental adaptability and long-term durability. These results strongly prove the innovation and practical value of the present invention, and provide a comprehensive and effective solution to the technical problems faced by traditional road marking paints.
[0087] Test Experiment Design: 1. Quick-drying performance test Experimental conditions: temperature 25±2°C, relative humidity 50±5% Experimental methods: (1) Apply the mixed coating on a standard glass plate with a wet film thickness of 400 μm.
[0088] (2) Use a BYK drying time recorder to measure the surface drying time and through drying time.
[0089] (3) Each sample was tested 3 times and the average value was taken.
[0090] 2. Anti-slip performance test Experimental conditions: temperature 25±2°C, relative humidity 50±5% Experimental methods: (1) The coating was applied on an asphalt board with a dry film thickness of 300 μm and cured naturally for 7 days.
[0091] (2) The slip resistance value (BPN) is measured under dry and wet conditions using a British pendulum tester.
[0092] (3) Each sample was tested at 5 points under dry and wet conditions and the average value was taken.
[0093] 3. Self-cleaning effect test Experimental conditions: outdoor natural environment, lasting 30 days Experimental methods: (1) Apply the coating to the concrete slab with a dry film thickness of 300 μm and allow to cure naturally for 7 days.
[0094] (2) Apply methyl orange solution (10 mg / L) evenly on the coating surface as a simulated pollutant.
[0095] (3) Place the sample outdoors under natural light conditions and measure the reflectance of the sample surface using a spectrophotometer every 5 days.
[0096] (4) Calculate the self-cleaning efficiency: η = (R - R0) / (R1 - R0) × 100% Where R is the reflectivity during testing, R0 is the reflectivity at initial contamination, and R1 is the reflectivity of the clean surface.
[0097] 4. Self-healing performance test Experimental conditions: temperature 25±2°C, relative humidity 50±5%, UV intensity 10mW / cm² Experimental methods: (1) The coating was applied on an aluminum plate with a dry film thickness of 400 μm and cured naturally for 7 days.
[0098] (2) Use a sharp blade to make a scratch with a length of 50 mm and a width of 0.5 mm on the coating surface.
[0099] (3) Place the sample under ultraviolet light and observe and record the degree of scratch healing using an optical microscope every 2 hours.
[0100] (4) Calculate the self-healing efficiency: η = (W0 - Wt) / W0 × 100% Where W0 is the initial scratch width, and Wt is the scratch width after t time.
[0101] 5. Durability test Experimental conditions: QUV accelerated weathering test, cycle of 8 hours UVA-340 lamp exposure (60±2°C) and 4 hours condensation (50±2°C) Experimental methods: (1) The coating was applied on an aluminum plate with a dry film thickness of 400 μm and cured naturally for 7 days.
[0102] (2) The samples were placed in a QUV aging test chamber for a total test time of 1000 hours.
[0103] (3) Take out samples every 200 hours and test the gloss retention, adhesion and abrasion resistance.
[0104] 6. Low temperature flexibility test Experimental conditions: Temperature -25±2°C Experimental methods: (1) The coating was applied on galvanized steel sheets with a dry film thickness of 400 μm and cured naturally for 7 days.
[0105] (2) Cool the sample at -25°C for 2 hours.
[0106] (3) Perform a bending test using a flexibility tester and record the minimum bending diameter at which the coating cracks.
[0107] The test results are shown in the following table: Table 1. Quick-drying performance and anti-slip performance test results sample Surface drying time (min) Drying time (min) Dry BPN Wet BPN Example 1 15 45 65 55 Example 2 12 40 70 60 Example 3 10 35 75 65 Example 4 13 42 72 62 Comparative Example 1 16 48 64 54 Comparative Example 2 14 44 68 58 Comparative Example 3 11 38 50 40 Comparative Example 4 20 55 65 50 Comparative Example 5 14 43 66 56 Comparative Example 6 13 41 69 59 Table 2. Self-cleaning effect test results (self-cleaning efficiency %) sample 5 days 10 days 15 days 20 days 25 days 30 days Example 1 35 55 70 80 85 88 Example 2 40 60 75 85 90 92 Example 3 45 65 80 88 93 95 Example 4 42 62 77 86 91 93 Comparative Example 1 33 52 68 78 83 86 Comparative Example 2 25 40 55 65 70 72 Comparative Example 3 38 58 73 83 88 90 Comparative Example 4 39 59 74 84 89 91 Comparative Example 5 37 57 72 82 87 89 Comparative Example 6 30 45 58 65 70 72 Table 3. Self-repair performance test results (self-repair efficiency %) sample 2 hours 4 hours 6 hours 8 hours 10 hours 12 hours Example 1 20 45 65 80 90 95 Example 2 25 50 70 85 93 97 Example 3 30 55 75 88 95 98 Example 4 28 52 72 86 94 97 Comparative Example 1 0 0 0 0 0 0 Comparative Example 2 18 40 60 75 85 90 Comparative Example 3 22 47 67 82 91 96 Comparative Example 4 23 48 68 83 92 96 Comparative Example 5 15 35 55 70 80 85 Comparative Example 6 24 49 69 84 92 96 Table 4. Durability test results sample Gloss retention rate (%) Adhesion(grade) Wear resistance (mg / 1000 times) Example 1 92 1 35 Example 2 94 0 30 Example 3 96 0 25 Example 4 95 0 28 Comparative Example 1 88 1 40 Comparative Example 2 85 1 38 Comparative Example 3 90 1 45 Comparative Example 4 91 1 37 Comparative Example 5 80 2 50 Comparative Example 6 86 1 42 Table 5. Low temperature flexibility test results sample Minimum bending diameter (mm) Example 1 6 Example 2 5 Example 3 4 Example 4 5 Comparative Example 1 7 Comparative Example 2 6 Comparative Example 3 6 Comparative Example 4 8 Comparative Example 5 10 Comparative Example 6 6 According to the above test results, Example 3 performs best and can be regarded as the best embodiment of the present invention.
[0108] The analysis and discussion are as follows: 1. Quick-drying performance: Examples 1-4 all showed excellent quick-drying performance, especially Example 3, whose surface drying time was only 10 minutes and actual drying time was 35 minutes. This was due to the rapid cross-linking reaction of the aqueous polyurethane dispersion and the water-dispersible isocyanate curing agent, as well as the synergistic effect of the intelligent temperature-sensitive thickener. In contrast, the drying time of Comparative Example 4 was significantly prolonged due to the lack of the intelligent temperature-sensitive thickener.
[0109] 2. Anti-skid performance: The anti-skid performance of Examples 1-4 is significantly better than that of the comparative example, especially Example 3, whose BPN values under dry and wet conditions are 75 and 65, respectively. This is mainly due to the addition of surface-modified anti-skid particles and the synergistic effect with the multifunctional silane coupling agent. The anti-skid performance of Comparative Example 3 is significantly reduced due to the lack of anti-skid particles.
[0110] 3. Self-cleaning effect: Examples 1-4 showed excellent and lasting self-cleaning effects, with self-cleaning efficiencies exceeding 88% after 30 days. Among them, Example 3 performed the best, reaching 95%. This is attributed to the efficient photocatalytic effect of iron-doped nano-titanium dioxide and the long-lasting hydrophobicity provided by hydrophobic nano-silicon dioxide. Comparative Examples 2 and 6 had significantly reduced self-cleaning effects due to the lack of these two key components.
[0111] 4. Self-repairing performance: Examples 1-4 all showed excellent self-repairing ability, with a self-repairing efficiency of more than 95% after 12 hours. This is mainly due to the effect of the light-responsive self-repairing microcapsules. Comparative Example 1 lacked this component and had no self-repairing ability at all.
[0112] 5. Durability: After 1000 hours of accelerated aging test, Examples 1-4 still maintain high gloss retention (>92%), excellent adhesion (0-1 level) and good abrasion resistance (<35 mg / 1000 times). This is due to the synergistic effect of the aqueous polyurethane dispersion, hyperbranched polyether modifier and light stabilizer. The durability of Comparative Example 5 is significantly reduced due to the lack of hyperbranched polyether modifier.
[0113] 6. Low temperature flexibility: Examples 1-4 exhibit excellent low temperature flexibility, with the minimum bending diameter not exceeding 6 mm. This is mainly due to the synergistic effect of the aqueous polyurethane dispersion and the hyperbranched polyether modifier, which enables the coating to maintain good flexibility at low temperatures. Comparative Example 5 has a significantly reduced low temperature flexibility due to the lack of a hyperbranched polyether modifier.
[0114] Unexpected technical effects: 1. Synergistic self-repair and self-cleaning: The combination of light-responsive self-repairing microcapsules and iron-doped nano-titanium dioxide in the present invention not only realizes the self-repair and self-cleaning functions of the coating, but also produces unexpected synergistic effects. The fresh surface exposed during the self-repair process is more conducive to the photocatalytic self-cleaning reaction, while the self-cleaning process can maintain the cleanliness of the coating surface and improve the self-repair efficiency. This dual effect greatly improves the overall performance and service life of the coating.
[0115] 2. Intelligent thermosensitive rheological regulation: The introduction of intelligent thermosensitive thickeners not only improves the construction performance of the coating, but also unexpectedly enhances the anti-slip performance of the coating. This is because the thermosensitive thickener maintains good fluidity during low-temperature construction, and rapidly thickens when the road temperature rises, forming a microscopic convex structure, which further improves the anti-slip effect of the coating.
[0116] 3. Multiple effects of hyperbranched polyether modifiers: Hyperbranched polyether modifiers not only improve the crosslinking density and flexibility of the coating, but also unexpectedly enhance the self-cleaning durability of the coating. This may be because the hyperbranched structure provides more functional end groups, which is conducive to interaction with other components and forms a more stable network structure.
[0117] 4. Environmental adaptability: The coating of the present invention exhibits excellent performance under various extreme environmental conditions (such as high temperature, low temperature, humidity, etc.).
[0118] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. Two-component quick-drying anti-skid self-cleaning road marking paint, characterized in that: It comprises component A and component B, wherein: Component A is made from the following raw materials in parts by weight: 30-50 parts of waterborne polyurethane dispersion Photoresponsive self-repairing microcapsules 5-10 copies 3-8 parts of iron-doped nano-titanium dioxide 8-15 parts of surface modified anti-skid particles Multifunctional silane coupling agent 1-3 parts pH adjuster 0.1-0.5 parts Bio-based defoamer 0.2-0.6 parts Intelligent temperature sensitive thickener 0.5-1.5 parts Broad-spectrum antibacterial agent 0.1-0.3 parts 10-40 parts of deionized water Component B is made from the following raw materials in parts by weight: 20-40 parts of water-dispersible isocyanate curing agent Hyperbranched polyether modifier 5-15 parts 1-3 parts of hydrophobic nano-silica Light stabilizer 0.5-1.5 parts 40-70 parts of deionized water.
2. The two-component quick-drying anti-skid self-cleaning road marking paint according to claim 1, characterized in that: The aqueous polyurethane dispersion has a solid content of 40 ± 1%, a pH value of 7.0-8.5, a viscosity (23°C) of 50-800 mPa·s, and an average particle size of 80-120 nm; The multifunctional silane coupling agent is N-[3-(trimethoxysilyl)propyl]-1,2-ethylenediamine, with a boiling point of 260°C, a flash point of 93°C, and a density (25°C) of 1.03 g / cm³.
3. The two-component quick-drying anti-skid self-cleaning road marking paint according to claim 1, characterized in that: The pH regulator is ammonium hydroxide, with a concentration of 28% aqueous solution; The broad-spectrum antibacterial agent is a mixture of 1,2-benzisothiazol-3(2H)-one and 2-methyl-4-isothiazoline-3-one, wherein the content of 1,2-benzisothiazol-3(2H)-one is 10-15%, and the content of 2-methyl-4-isothiazoline-3-one is 2-5%.
4. The two-component quick-drying anti-skid self-cleaning road marking paint according to claim 1, characterized in that: The hyperbranched polyether modifier has a hydroxyl value of 230-250 mg KOH / g and a viscosity (23°C) of 3000-5000 mPa·s; The hydrophobic nano-silica is pyrolytic silica treated with hexamethyldisilazane, with a specific surface area of 195-245 m² / g, an average particle size of 7 nm, and a carbon content of 3.0-4.0%.
5. The two-component quick-drying anti-skid self-cleaning road marking paint according to claim 1, characterized in that: The active ingredient content of the light stabilizer is 52-56%, and the pH value is 6.0-8.0; The water-dispersible isocyanate curing agent is a water dispersion of hexamethylene diisocyanate, with an NCO content of 16.5-17.5% and a viscosity (23°C) of 500-2500 mPa·s.
6. The method for preparing the two-component quick-drying anti-skid self-cleaning road marking paint according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Preparation of component A: First, add waterborne polyurethane dispersion into the reactor and stir at a speed of 300-400 rpm; Secondly, add the photoresponsive self-healing microcapsules and stir for 30 minutes; Then, iron-doped nano-titanium dioxide was added and stirred for 45 minutes; Again, add the surface modified anti-skid particles and stir for 30 minutes; Next, add the multifunctional silane coupling agent, pH adjuster, bio-based defoamer and intelligent temperature-sensitive thickener in sequence, stirring for 10 minutes after each addition of raw materials; Finally, a broad-spectrum antimicrobial agent was added, stirred for 15 minutes, and deionized water was added to adjust the solid content to 55-60%, stirred for 30 minutes, and filtered through a 100-mesh sieve to obtain component A; (2) Preparation of component B: First, add water-dispersible isocyanate curing agent into the reaction kettle, stirring at a speed of 200-300 rpm; Secondly, add the hyperbranched polyether modifier and stir for 20 minutes; Then, hydrophobic nano-silica was added and stirred for 30 minutes; Again, add the light stabilizer and stir for 15 minutes; Finally, deionized water was added to adjust the solid content to 40-45%, stirred for 20 minutes, and filtered through a 200-mesh sieve to obtain component B.
7. The preparation method according to claim 6, characterized in that: The method for preparing the light-responsive self-repairing microcapsules comprises the following steps: (1) preparing an oil phase: mixing 5-10 parts by weight of dicyclopentadiene and 0.1-0.3 parts by weight of a light-responsive Grubbs catalyst at 20-25° C., stirring at a speed of 300-400 rpm for 15-20 minutes; (2) preparing an aqueous phase: dissolving 1-2 parts by weight of polyvinyl alcohol in 100-150 parts by weight of deionized water, stirring at a speed of 500-600 rpm, a temperature of 60-70° C., and a time of 30-40 minutes; (3) preparing a monomer mixture: mixing 15-25 parts by weight of methyl methacrylate and 1-3 parts by weight of glycidyl methacrylate, and adding 0.2-0.5 parts by weight of azobisisobutyronitrile; (4) Emulsification: slowly add the oil phase into the water phase and shear emulsify at 60-70°C at a speed of 1000-1200 rpm for 15-20 minutes; (5) Suspension polymerization: Slowly add the monomer mixture dropwise into the emulsion and react at 70-75°C with stirring (400-500 rpm) for 3-4 hours; (6) Cooling: Cooling the reaction mixture to room temperature; (7) Filtration, washing, and drying: Filter using a Buchner funnel, wash with deionized water 3-5 times, and vacuum dry at 40-50°C for 12-24 hours.
8. The preparation method according to claim 6, characterized in that: The preparation method of the iron-doped nano titanium dioxide comprises the following steps: (1) Preparation of precursor solution: dissolve 20-30 parts by weight of tetrabutyl titanate in 80-100 parts by weight of anhydrous ethanol, stir at 300-400 rpm, and stir at room temperature for 30 minutes; at the same time, dissolve 0.5-1.5 parts by weight of ferric nitrate in 20-30 parts by weight of deionized water; (2) Hydrolysis: slowly add the iron salt solution to the titanate solution, increase the stirring speed to 600-800 rpm, and react at room temperature for 1-2 hours; (3) Aging: The mixture was aged at 60-70°C with stirring (200-300 rpm) for 4-6 hours; (4) Hydrothermal treatment: the aged sol is transferred to a polytetrafluoroethylene-lined autoclave and treated at 180-200°C for 8-12 hours; (5) Cooling, filtering, and washing: Cool naturally to room temperature, filter, and wash with deionized water and anhydrous ethanol 3-5 times each; (6) Drying and calcining: drying at 60-70°C for 12-24 hours, and then calcining at 400-500°C for 2-3 hours; (7) Grinding: Grind the calcined sample to an average particle size of 20-30 nm.
9. The preparation method according to claim 6, characterized in that: The preparation method of the surface-modified anti-skid particles comprises the following steps: (1) Pretreatment: 100 parts by weight of α-alumina was vacuum dried at 120-130° C. for 4-6 hours; (2) Silanization: Add the pretreated alumina and 200-250 parts by weight of anhydrous toluene to a three-necked flask, stir and disperse (300-400 rpm) for 10-15 minutes; slowly add 3-5 parts by weight of 3-glycidyloxypropyltrimethoxysilane, raise the temperature to reflux (about 110-120°C), and stir and react for 4-6 hours; (3) Cooling and filtration: Cool naturally to room temperature and filter; (4) Washing: Wash with anhydrous toluene 3 times, then wash with anhydrous ethanol 2 times; (5) Drying: Vacuum drying at 60-70°C for 12-24 hours.
10. The preparation method according to claim 6, characterized in that: The preparation method of the intelligent temperature-sensitive thickener comprises the following steps: (1) Preparation of monomer solution: In a three-necked flask, 15-20 parts by weight of N-isopropylacrylamide and 1-2 parts by weight of acrylamide are dissolved in 150-200 parts by weight of deionized water, and nitrogen is passed through for 15-20 minutes to remove oxygen; (2) Preparation of initiator solution: dissolve 0.1-0.2 parts by weight of ammonium persulfate in 10-15 parts by weight of deionized water; (3) Polymerization reaction: Heat the monomer solution to 60-65°C and control the stirring speed at 300-400 rpm; slowly add the initiator solution dropwise and react for 4-6 hours; (4) Termination of the reaction: Cool the reaction mixture to room temperature and allow air to flow for 10-15 minutes; (5) Purification: The reaction product was poured into excess acetone for precipitation, filtered, and washed with acetone three times; (6) Drying: Vacuum drying at 40-50°C for 24-48 hours.
Citation Information
Patent Citations
High-adhesion wear-resisting, skid-resisting and weather-resisting sport field special coating and preparation method thereof
CN104987789A
Aqueous dual-component quick-drying top coat and application thereof
CN106675382A
Ship antifouling paint and preparation method thereof
CN112625552A
Super-hydrophobic composite coating and preparation method and application thereof
CN112662315A
Preparation method of temperature-sensitive tackifying suspending agent for well cementation cement paste
CN112724413A